Insights into the Mechanical Behaviour of a Layered Flexible Tactile Sensor - Castellanos-Ramos, Julián; Navas-González, Rafael Jesús; Fernández, Iván; Vidal-Verdú, Fernando (MDPI Open Access Journal, 2015)
This paper shows realizations of a piezoresistive tactile sensor with a low cost screen-printing technology. A few samples were fabricated for different materials used as insulator between the conductive layers and as top layer or cover. Both can be used to tune the sensitivity of the sensor. However, a large influence is also observed of the roughness at the contact interface on the sensitivity and linearity of the output, as well as on mismatching between the outputs from different taxels. The roughness at the contact interface is behind the transduction principle of the sensor, but it also limits its performance if the wavelength of the roughness is comparable or even longer than the size of the contacts. The paper shows experimental results that confirm this relationship and discusses its consequences in sensor response related to the materials chosen for the insulator and the cover. Moreover, simulations with FEA tools and with simple models are used to support the discussions and conclusions obtained from the experimental data. This provides insights into the sensor behaviour that are shared by other sensors based on the same principle.
Keywords: Polímeros conductores; Tactile sensor; Screen-printing technology; Conductive polymers